A Preliminary Study on the Implementation of ISO 45001:2018 for Gemas – Johor Bahru Electrified Double Track Project - Kamarulzaman, Farah Najwa; A.Kadir, Zuritah; Ismail, Nazaruddin (Progress in Engineering Application and Technology, 2023)
Occupational health and safety (OHS) management are a subset of public health that focuses on improving workplace health and safety. It examines worker injury and sickness patterns and makes recommendations for reducing the risks and hazards they face on the job. This study aims to investigate the level of readiness for leadership, support and operation are ready to implement for ISO 45001:2018 to Gemas – Johor Bahru Electrified Double Track Project. For the first objective, literature review was conducted to investigate ISO 45001:2018 occupational health and safety management system Certification Programme for construction double track project. Second objective was to identify the readiness of ISO 45001:2018 occupational health and safety management Certification Programme implementation for Gemas - Johor Bahru Electrified double track project. In order to achieve the objectives, a questionnaire was constructed and disseminated to 30 respondents (n=30). Data collected was analysed using SPSS version 27. The data was reliable based on Cronbach’s Alpha value which is above 0.7. Descriptive analysis was done, and it was found that the mean score is high for leadership (mean=4.47), support (mean=4.54) and operation (mean=4.45). It can be proven that the organization, top management, staff, and workers are ready to implement the ISO 45001:2018 on this project. It was also found that the significance correlations of leadership, support, and planning between ISO 45001:2018 was significance of the 2-tailed value was less than 0.05 (p-value